Large-Dynamic-Range Dual-Parameter Sensor Using Broad FSR Multimode Photonic Crystal Nanobeam Cavity - Chao Wang; Zhongyuan Fu; Fujun Sun; Jian Zhou; Huiping Tian (IEEE Photonics Journal)
We theoretically propose an ultracompact large-dynamic-range dual-parameter sensor using a broad free spectral range (FSR) multimode photonic crystal nanobeam cavity (MM-PCNC). In the multimode regime, each resonant mode is exploited as an independent sensing channel. Broad FSR (>100 nm) is achieved by PCNC consisting of composite lattice cells (CLCs). The CLC is designed for the special bands property enabling the excitation of multiple resonant modes with broad FSR possible. Notably, an interesting stability of the mirror strength is achieved for the CLC, which provides a new perspective for further optimizing ultracompact PCNCs with high quality factor (Q) and broad FSR. Additionally, due to the special structure of the CLC, the energy of resonant modes can be effectively localized in the low dielectric area, which are quantitatively indicated by the calculated optical overlap integrals, resulting in strong light-matter interactions. Simultaneous detection of the refractive index (RI) and temperature is conducted by multiplexly using the fundamental mode and the first-order mode of the PCNC, with the optimal RI and temperature sensitivities of 413 nm/RIU and 62.9 pm/K, and the corresponding detection limits of 7.2 × 10 −6 RIU and 0.117 K, respectively. Large-dynamic-range sensing supported by the broad FSR is also analyzed. Therefore, due to the broad FSR, high Q, and ultracompact size, the proposed MM-PCNCs are promising platforms for realizing applications such as large-dynamic-range detection, high integration large scale on-chip sensing, and multifunctional detection in the future.